2005
DOI: 10.1021/ma051958n
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of Sulfonated Poly(styrene-b-isobutylene-b-styrene) Triblock Copolymers at High Ion-Exchange Capacities

Abstract: Public Reporting Burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comment regarding this burden estimate or any other aspect of this collection of information, including suggesstions for reducing this burden, Transport Properties of Sulfonated Poly(styrene-b-isobutylene-b-styrene) Tribloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
206
5
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(224 citation statements)
references
References 43 publications
10
206
5
3
Order By: Relevance
“…20,30,47 The uniqueness of these materials can be attributed to the fact that they can self-assemble into ordered periodic microstructures, [29][30][31][32]37,65 which offers the potential of gaining an extremely valuable insight into the effects of nanoscale morphology on proton transport. In these systems, the structural aspects, such as the types of self-assembled structures, the width of the hydrophilic phases, and the orientation of the water channels located within the hydrophilic domains become highly relevant parameters for understanding the transport properties of PEMs.…”
Section: Feature Articlementioning
confidence: 99%
See 2 more Smart Citations
“…20,30,47 The uniqueness of these materials can be attributed to the fact that they can self-assemble into ordered periodic microstructures, [29][30][31][32]37,65 which offers the potential of gaining an extremely valuable insight into the effects of nanoscale morphology on proton transport. In these systems, the structural aspects, such as the types of self-assembled structures, the width of the hydrophilic phases, and the orientation of the water channels located within the hydrophilic domains become highly relevant parameters for understanding the transport properties of PEMs.…”
Section: Feature Articlementioning
confidence: 99%
“…It has been widely reported that the phase-separated hydrophobic phases can provide effective mechanical support while the well-arranged nanometer-scale hydrophilic domains facilitate ion transport by means of confinement effects (at the same ion exchange capacity (IEC) value, ions confined within microphase-separated hydrophilic phases are in close proximity, compared to their random analogues). 8,10,28,29 Examples of such polymers include sulfonated poly(styrene-b-isobutylene-b-styrene), 30,31 sulfonated poly(styrene-b-methylbutylene), 28,32 sulfonated poly(ether ether ketone)-b-poly(ether sulfone), 33,34 and sulfonated poly([vinylidene difluoride-chlorotrifluoro ethylene]-gstyrene). 19,35,36 Note in passing that although much of the research on the sulfonated polymers indicated that morphology is important in determining transport properties, the achievement of well-defined structures with long-range order is lacking and it has been the subject of the current studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductivity is comparable to that of Nafion and the methanol permeability is strongly reduced [189]. A systematic study dealing the correlation between the structure and conductivity was recently reported using sulfonated SIBS [195,201] using a range of degrees of sulfonations and different solvents to cast the membranes. Well-defined cylindrical and lamellar self-assembled ion channels could be obtained but typically they are parallel to membrane surfaces, leading to reduced conductivity across the mem- Fig.…”
Section: Self-assembled Protonically Conducting Polymersmentioning
confidence: 99%
“…3.5 Sulfonated polystyrene-b-polyisobutene-b-polystyrene leads to well defined self-assembled structures at low levels of sulfonation and the domains are aligned parallel to the membrane. Increasing the sulfonation level leads to less periodic structures but also to increased proton transport [201].…”
Section: Self-assembled Protonically Conducting Polymersmentioning
confidence: 99%